Understanding the relationships between swine behavior, physiology and management to improve animal welfare, reduce in-transit losses and improve meat quality in swine - Edwards, Lily Nowell, author; Grandin, Temple, advisor; Engle, Terry E., advisor; Rollin, Bernard E., committee member; Anderson, David B., committee member (Colorado State University. Libraries, 2009)
The objective of these studies was to determine the relationship between pre-slaughter management, physiological measures, and meat quality using commercial swine marketing practices. Experiments 1 & 2 were conducted to determine the effects of distance moved at the farm, time of lairage in holding pens prior to slaughter and distance moved from lairage pens to the stunning area on blood lactate concentration ([LAC]), rectal temperature and meat quality. Both [LAC] and temperature changed during the marketing process (P< 0.0001). The highest [LAC]s were observed at loading and exsanguination. Longer distance resulted in higher [LAC] during loading (Exp. 2). Unexpectedly, longer rest resulted in higher [LAC]s at exsanguination (Exp 1 & 2) and at the end of lairage (Exp. 2). An increase in [LAC] during loading reduced glycolytic potential (Exp. 2) and had a positive impact on meat quality measures, i.e. decreased drip loss, increased 24 hr pH and trends for lower L* and higher visual muscle color score (Exp 1 &2). Specific measurements of pre-stun handling, jamming, rearing, vocalization, electric prod use, backing up, were found to be correlated with exsanguination [LAC] (P<0.05). Experiment 3 evaluated the persistence of blood changes in swine during the marketing process following alteration of dietary electrolyte balance (dEB). Experimental pigs were assigned to a Low (121 meq/kg) or High (375 meq/kg) dEB diet ad libitum for 3 days prior to slaughter. Prior to transport, animals were fasted in the barn for 10 h, then shipped to the plant, rested for 8 h and slaughtered. Blood was sampled four times, initial and final weights were obtained and meat quality parameters were measured. Increasing dEB had no adverse effects on growth performance, meat quality, carcass yield or incidence of pars esophageal ulcer scores. Exsanguination [LAC] was negatively correlated to 60 min pH (r = -0.32, P = 0.0004) and positively correlated (r = 0.21, P = 0.02) to drip loss. These results suggest that exsanguination [LAC] is predictive of the rate of early post-mortem metabolism. This study demonstrated that the effect of dEB on blood parameters was not maintained following a 10 h feed withdrawal (P > 0.22). Therefore, it is likely that the animal‟s ability to withstand any increased metabolic acid load associated with the stress of transport was lost following feed withdrawal. This research supports the use of LAC as a sensitive tool to determine changes in handling and management. These studies emphasized the impact that pre-slaughter management has on physiological parameters of swine throughout the entire marketing process.
Department Head: William R. Wailes.